2020
DOI: 10.1097/md.0000000000019907
|View full text |Cite
|
Sign up to set email alerts
|

Consolidation period of 18 months no better at promoting off-treatment durability in HBeAg-positive chronic hepatitis B patients with tenofovir disoproxil fumarate treatment than a 12-month period

Abstract: There has been no clear consensus on the optimal consolidation periods following HBeAg seroconversion (SC) in HBeAg-positive chronic hepatitis B (CHB) patients. Our study aimed to prospectively compare relapse rates between 12 months’ and 18 months’ consolidation periods to see whether or not there is beneficial durability of tenofovir disoproxil fumarate (TDF) therapy with longer consolidation periods. We enrolled a total of 137 HBeAg-positive Asian CHB patients treated with TDF monotherapy. Forty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 36 publications
0
10
0
1
Order By: Relevance
“…1 ). [12] , [13] , [14] , [17] , [18] , [19] , 27 , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] One of the studies involved two distinct cohorts, of which one consisted exclusively of individuals with prior severe acute exacerbation and the other consisted of patients who had never experienced such an event. 31 Therefore, 50 studies with 51 cohorts were included in the meta-research analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 ). [12] , [13] , [14] , [17] , [18] , [19] , 27 , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] One of the studies involved two distinct cohorts, of which one consisted exclusively of individuals with prior severe acute exacerbation and the other consisted of patients who had never experienced such an event. 31 Therefore, 50 studies with 51 cohorts were included in the meta-research analysis.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 46 of 50 studies reported data on severe flares or hepatic decompensation, but heterogeneously defined them as hyperbilirubinemia (without or without concurrent coagulopathy), ascites, encephalopathy, and/or variceal bleeding, in addition to abrupt elevation of serum ALT. [12] , [14] , [17] , [18] , [19] , 27 , [30] , [31] , [32] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , 69 , 70 , 72 The definition of hyperbilirubinemia was also heterogeneous and could be a level of serum bilirubin ≥2 mg/dl, >3 mg/dl, and >2.5x the upper limit of normal. Similarly, coagulopathy was heterogeneously defined by prolongation of prothrombin time (PT) >3 seconds or an international normalized ratio >1.5 ( Table S7 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, viral activity and ALT fluctuations persist within the HBeAg-negative chronic hepatitis phase of infection due to genomic mutations altering HBeAg expression [ 11 ]. Quantified HBeAg levels have also been shown in the literature to be associated with HBeAg seroconversion and pegylated-interferon α (peg-IFN) and nucleos(t)ide analogue (NA) treatment response [ 12 , 13 , 14 , 15 ]. However, there is no commercially available quantitative method and no standardization between laboratory-developed methods.…”
Section: Traditional Hbv Diagnostic Testingmentioning
confidence: 99%
“…Although the approach of finite NA treatment is not completely uniform, there is a consistent agreement among different guidelines: finite NA therapy was suggested in not-cirrhotic patients with undetectable levels of HBV DNA(on three separate occasions, 6 months apart) after 12–18 months from HBeAb seroconversion (consolidation therapy) [ 52 ]. The Asian guidelines, in contrast to EASL and AASLD, consider finite NA treatment also in patients with cirrhosis [ 4 , 53 , 54 , 55 ].…”
Section: Finite Nucleos(t)ide Analog Therapymentioning
confidence: 99%